EU Structural Funds in the Baltic Countries-Useful or Harmful. Euroopa Liidu struktuurifondid Balti riikides- kasulikud või kahjulikud? - Varblane, Urmas (Estonian Discussions on Economic Policy, 2016)
The current article is focused on the role of financial assistance from the European Union in the budgets of the three Baltic countries. They all have seriously benefitted from the support of EU structural funds, which have reached close to five per cent of their GDP. Based on the case of higher education research funding, the article argues that the Baltic countries overlook the additionality principle of the European Union cohesion policy. Structural funds are replacing the Baltic countries’ own funding. During the current EU programming period between 2014 and 2020 the exit strategies should be prepared by the governments of Baltic countries in order to be able to finance research with significantly lower support from EU cohesion funds. The precondition is that instead of a short-run view, in the coalition treaties of the Baltic governments, a long-term strategy for how to move toward knowledge intensive economies is also needed. The first and most urgent need is to improve the quality of use of the EU support funds by all three countries in order to support longrun productivity growth and increase the competitiveness of the Baltic countries.